Clinical Outcomes of Women With Recurrent or Persistent Uterine Leiomyosarcoma. Issue 8 (1st October 2014) - Rauh-Hain, Jose Alejandro; Hinchcliff, Emily M.; Oduyebo, Titilope; Worley, Michael J.; Andrade, Carolina A.; Schorge, John O.; George, Suzanne; Muto, Micheal G.; del Carmen, Marcela G.
Abstract : Objectives: This study aimed to identify prognostic factors influencing the outcome of recurrent or persistent uterine leiomyosarcoma (ULMS). Methods: All patients with recurrent or persistent ULMS who underwent treatment at the participating institutions between January 2000 and December 2010 were identified from the tumor registry. The Kaplan-Meier method was used to generate overall survival data. Factors predictive of outcome were compared using the log-rank test and Cox proportional hazards model. Results: One hundred fifteen (68.8%) patients who had recurrent/persistent disease were identified, 40 (34.8%) had persistent disease, and 75 (65.2%) had a recurrence. Median follow-up time was 24.9 months. The 5-year postrelapse survival rate was 15% and was not significantly different between women with recurrent or persistent disease (16% vs 13%; P = 0.1). Variables identified affecting the 5-year postrelapse survival rate included low number of mitosis at the time of diagnosis (<25, 25% vs 5%; P = 0.002), time to relapse from original diagnosis (≤6 vs >6 months, 8% vs 22%; P = 0.003)), and surgical treatment (17% vs 12%; P = 0.01). Age, stage, chemotherapy at time of original diagnosis or at the time of relapse, site of recurrence, and single versus multiple sites of recurrence were not associated with survival. In a multivariate Cox regression model, only low number of mitosis (hazard ratio, 0.5; 95% confidence interval, 0.3–0.8, P = 0.02) was identified as a predictor of overall survival. Conclusions: The prognosis of patients with recurrent/persistent ULMS is, in general, poor. Women who have low number of mitosis at the time of diagnosis seemed to have better postrelapse survival.